Effects of Sacubitril/Valsartan on Exercise Capacity in Patients with Heart Failure with Reduced Ejection Fraction and the Role of Percentage of Delayed Enhancement Measured by Cardiac Magnetic Resonance in Predicting Therapeutic Response: A Multicentre Study - Cinzia Nugara; Francesco Giallauria; Giuseppe Vitale; Silvia Sarullo; Giovanni Gentile; Francesco Clemenza; Annamaria Lo Voi; Antonino Zarcone; Elio Venturini; Gabriella Iannuzzo; Andrew JS Coats; Filippo M Sarullo (Cardiac Failure Review)
Background: This study aims to evaluate the cardiopulmonary effects of sacubitril/valsartan therapy in patients with heart failure with reduced ejection fraction (HFrEF), investigating a possible correlation with the degree of myocardial fibrosis, as assessed by cardiac magnetic resonance. Methods: A total of 134 outpatients with HFrEF were enrolled. Results: After a mean follow-up of 13.3 ± 6.6 months, an improvement in ejection fraction and a reduction in E/A ratio, inferior vena cava size and N-terminal pro-B-type natriuretic peptide levels were observed. At follow-up, we observed an increase in VO2 peak of 16% (p<0.0001) and in O2 pulse of 13% (p=0.0002) as well as an improvement in ventilatory response associated with a 7% reduction in the VE/VCO2 slope (p=0.0001). An 8% increase in the ΔVO2/Δ work ratio and an 18% increase in exercise tolerance were also observed. Multivariate logistic regression analysis showed that the main predictors of events during follow-up were VE/VCO2 slope >34 (OR 3.98; 95% CI [1.59–10.54]; p=0.0028); ventilatory oscillatory pattern (OR 4.65; 95% CI [1.55–16.13]; p=0.0052); and haemoglobin level (OR 0.35; 95% CI [0.21–0.55]; p<0.0001). In patients who had cardiac magnetic resonance, when delayed enhancement >4.6% was detected, a lower response after sacubitril/valsartan therapy was observed as expressed by improvement in ΔVO2 peak, O2 pulse, LVEF and N-terminal pro-B-type natriuretic peptide. No significant differences were observed in ΔVO2/Δ work and VE/VCO2 slope. Conclusion: Sacubitril/valsartan improves cardiopulmonary functional capacity in HFrEF patients. The presence of myocardial fibrosis on cardiac magnetic resonance is a predictor of response to therapy.